Impacts Of Fishing On The Rural Household Income; Evidence From Ethiopian Rift-Valley - Alemayehu Abebe Wake; Teferi Tolera; Tamiru Chalchisa Geleto (Cogent Economics & Finance, 2022)
Fish farming is a vital resource to fight poverty and food insecurity through the diversification of income sources. However, little has been investigated on its actual contributions to increase household income. This study envisages the impacts of fishing on the household income in Lume District, Ethiopian Rift valley. The quasi-experimental research design was used. Both qualitative and quantitative data were collected from both primary and secondary sources. Two-stage stratified sampling procedures were employed and about 374 sample households (about 202 non-fishing and 172 fishing households) were randomly selected. Structured interview schedules, key informant interviews, and focused group discussions were employed to collect the relevant data. Descriptive statistics (frequency, percentage, mean, and standard deviation) and the Propensity score matching method were employed to analyze the data. STATA V.13 software was used as an analytical tool. Fishing and non-fishing households had earned an annual income of about 36,914.85 and 31,768.43 Ethiopian Birr per year respectively. The model output reveals that the average treatment effect on the treated is about ETB 5146.42 and the mean difference in the average effect of the treatment on the treated between the matched treatment and control groups was found to be statistically significant at a 5% significance level. Overall, participation in fishing has generated about a 7.5% increase in farm annual income of treated households over control groups. It can be concluded that participation in fishing has brought a positive and significant impact on improving a household's annual income status in the study area. Therefore, special attention should be given by governmental and non-governmental organizations to improve the fish and aquaculture sector in the area through the introduction and dissemination of innovations that can enhance fish productivity in the study area.
Keywords: 330; Ethiopia; fish production; income; propensity score matching